Saving Mr. Banks [videorecording (DVD)] - Thompson, Emma; Hanks, Tom; Giamatti, Paul; Schwartzman, Jason, 1980-; Whitford, Bradley; Farrell, Colin, 1976-; Novak, B. J., 1979- (Disney DVD.)
When P.L. Travers travels from London to Hollywood in 1961 to finally discuss Walt Disney's desire to bring her beloved character, Mary Poppins to the motion picture screen (a quest he began in the 1940s as a promise to his two daughters), Disney meets a prim, uncompromising sexagenarian not only suspect of the impresario's concept for the film, but a woman struggling with her own past. During her stay in California, Travers' reflects back on her difficult childhood in 1906 Australia.